GPU accelerated blockchain over key‐value database transactions. Issue 1 (4th March 2022) - Iliakis, Konstantinos; Koliogeorgi, Konstantina; Litke, Antonios; Varvarigou, Theodora; Soudris, Dimitrios
Abstract: Blockchain is a distributed ledger based on peer‐to‐peer networks, originally used for crypto‐currency systems. Blockchains are being used as an enabling technology for decentralised applications in the areas of Internet‐of‐Things, finance, supply‐chain and others. Consistency, data privacy, performance, and energy efficiency are of paramount importance in such applications. The full nodes of public, permissionless blockchains undertake the task of verifying the transactions generated by the network. Full nodes perform operations such as confirming balances, transactions, and history, i.e. mostly database search queries. Consequently, their throughput is crucial for the performance of blockchain systems. In this work, the benefits of accelerating the blockchain search and insert queries by leveraging GPU platforms are studied. An extensive comparison between the most dominant utilized database is provided, i.e. LevelDB, and MegaKV, a high‐performance GPU‐accelerated database. Realistic operations that take place in blockchain systems are emulated and evaluated over representative scenarios, showing three orders of magnitude gains in throughput and energy efficiency without compromising the security aspect. The extensive comparison between LevelDB and MegaKV indicates that GPU acceleration is an effective solution for runtime and energy efficiency enhancement of blockchain systems, and the integration of the two technologies is a promising field of research.